Two New Species of Stenamma (Hymenoptera: Formicidae) from Indian Himalaya With a Revised Key to the Palaearctic and Oriental Species - Himender Bharti; Irfan Gul; Yash Paul Sharma (Sociobiology, 2014)
Two new species of genus Stenamma viz Stenamma wilsoni sp. nov. and Stenamma jhitingriense sp. nov. are described from Indian Himalaya. This adds two more species to the genus from Indian Himalaya, with only Stenamma kashmirense Baroni Urbani, 1977 described earlier. A revised key to 26 species from Palaearctic and Oriental is provided here with.